2012
DOI: 10.1111/j.1751-1097.2012.01173.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐Intensity 405 nm Light Inactivation of Listeria monocytogenes

Abstract: The antimicrobial properties of light is an area of increasing interest. This study investigates the sensitivity of the significant foodborne pathogen Listeria monocytogenes to selected wavelengths of visible light. Results demonstrate that exposure to wavelength region 400-450 nm, at sufficiently high dose levels (750 J cm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 43 publications
2
62
3
Order By: Relevance
“…This indicates that efficacy of LED illumination may depend on serotype and strain within the same serotype. In contrast, Endarko et al (20) reported similar sensitivities to 405-nm LED illumination among Listeria ivanovii, L. monocytogenes, and Listeria seeligeri in PBS, while the sensitivities of S. Enteritidis, S. sonnei, L. monocytogenes, and E. coli differed. Results from another study showed that treatment with a 405-nm LED in PBS caused 5-log reductions of L. monocytogenes, S. sonnei, and E. coli O157:H7 at different doses (21).…”
Section: Discussionmentioning
confidence: 84%
“…This indicates that efficacy of LED illumination may depend on serotype and strain within the same serotype. In contrast, Endarko et al (20) reported similar sensitivities to 405-nm LED illumination among Listeria ivanovii, L. monocytogenes, and Listeria seeligeri in PBS, while the sensitivities of S. Enteritidis, S. sonnei, L. monocytogenes, and E. coli differed. Results from another study showed that treatment with a 405-nm LED in PBS caused 5-log reductions of L. monocytogenes, S. sonnei, and E. coli O157:H7 at different doses (21).…”
Section: Discussionmentioning
confidence: 84%
“…These results suggest that blue light triggers the formation of ROS and that these species have an inhibitory effect on growth, presumably because they cause oxidative damage of macromolecules in the cell (36). Previous studies have suggested the link between killing of bacteria by high-intensity visible light and ROS production (25,37). The mechanisms underlying ROS production remain to be elucidated, but endogenous porphyrins have been implicated in light inactivation studies with other bacteria (38)(39)(40).…”
Section: Discussionmentioning
confidence: 92%
“…One possible interpretation of these data was that oxygen levels in the medium were influenced by the population cell density, and that this variable might influence the sensitivity to blue light, since other studies have reported that light can lead to the generation of reactive oxygen species (ROS) (25,35). To investigate this hypothesis, we measured the inhibitory effect of blue light on cells grown in BHI medium containing the ROS scavenger dimethylthiourea (DMTU).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations